Complete twin suppression in oriented NH2-MIL-125 film via facile coordination modulation. Issue 63 (18th July 2022) - Sun, Yanwei; Liu, Liangliang; Ji, Taotao; Yan, Jiahui; Liu, Yi
Abstract : A facile competitive metal ion-based coordination modulation strategy was developed for complete twin suppression in oriented c -oriented NH2 -MIL-125 film. Abstract : Complete suppression of twin crystal formation in oriented metal–organic framework (MOF) film remains a great challenge. In this study, we successfully avoided the twin generation in c -oriented NH2 -MIL-125 film through simple competitive metal ion-based coordination modulation. Simultaneously, relevant mechanism associated with twin suppression was elucidated.